La sinestesia en las Termas de Piedra, Montaña – Piedra – Agua (2011)
This article wants to show the Stone thermal Baths as a result of a work of ideas of the architect Peter Zumthor. Indeed, the central argument of this research is the synesthesia as axis of unity and a characteristic determinant for the great work of architecture. Based on this central thesis, we look for the comprehension of the term of Synesthesia, besides the architectonic work. This personal vision is based on a research of the comprehension of the site and the design architect. Following these lines of study this text is composed by three parts, which are: mountain, stone and water. These parts assume the role of displaying our senses in the site in question.